Amanat Konstitusi Dalam Penyelenggaraan Pilkada Di Masa Pandemi Covid-19 Dengan Menjaga Protokol Kesehatan - Merta, M. Martindo; Pirmansyah, Redi; Junaidi, Junaidi (Lex Librum : Jurnal Ilmu Hukum, 2024)
The government consisting of the Ministry of Home Affairs, the DPR RI, the KPU, and Bawaslu agreed to organize pilkada in pandemic times. The government also issued large amounts of funds from the state and regional cash, which lasted from the beginning to the end of the Pilkada implementation process to meet the technical needs of the industry. The following policy has many advantages and disadvantages. But the optimism of the government requires the support of the public and all the parties involved in order to succeed Pilkada. Pilkada in the midst of the election Covid-19 pandemic has had a positive impact and also a negative impact. The positive impact is the implementation of existing regulations, the exercise of constitutional rights of Pilkada participants and the public remains running, thus reducing the practice ofining the government of the region that is too led by temporary officials, hindering the preparation of budgets. Meanwhile, the negative impacts include an increased risk of becoming infected with Covid-19, the likelihood of increasing vulnerability to fraud, and the rejection of scam can increase the number of non-voters.